Web-Based Management System for Pura Kencana Sports Centre - Zarif Nor Aiman bin Jafridin; Salamat, Mohamad Aizi (Applied Information Technology And Computer Science, 2023)
In most companies, the introduction of web-based management system solutions results in the simplification of business procedures. Problematic for Pura Kencana Sports Centre is the paper-based method of the management system. This increases the likelihood of duplicate bookings and lost customer information at Pura Kencana Sports Centre. To solve this problem, the Pura Kencana Sports Centre Management System was developed to manage their sports facilities, with a focus on court booking, and to evaluate the system’s overall performance. The system is based on ZF2, PHP, and MySQL and uses HTML5 extensively without needing support for obsolete browsers. The Agile Model was used to develop the system. It is hoped that the Pura Kencana Sports Centre Management System would assist the customers and management of the Pura Kencana Sports Centre in gathering information, performing the booking process systematically, and being well-integrated with any payment gateway in future.